HUBUNGAN KARAKTERISTIK IBU DENGAN STATUS GIZI BALITA YANG BERKUNJUNG DI PUSKESMAS BAHU MANADO - Labada, Agesti; Ismanto, Amatus Yudi; Kundre, Rina (JURNAL KEPERAWATAN, 2016)
Abstract: A toddler is the growth of the body and the brain is very rapidly in achieving the function. So that needs of nutrition toddlers need to be considered as malnourishement can affect the of Â brain children. In fact, the brain grow up for the toddler. The purpose of this researchto determine the characteristics of the mother relationship with the status nutrition infants who visit in the health center of The Bahu Manado.Samples on this research is using purposive sampling so that the sample in this study that 98 respondents. The design research used is descriptive analytic cross-sectional design and the data collected from respondents using the observation. The results of research based on the test Pearson Chi Square there is no significant relationship between age and nutritional status of toddlers (p = 0513), there is a significant relationship between education and nutrition status of toddlers (p = 0.001), there was no significant between jobs mother's with the status nutrition toddlers (p = 0432), there is a significant between the number of children and the nutritional status of toddlers (p = 0.000). The Conclusions of the study showed that there no relationship the mother's age with nutritional status of toddlers, there is a relationship the mother's education with the nutritional status of toddlers there is no relationship work mother's with nutritional status of toddlers, there is a relationship there are the number of children with nutrition status of toddlers. The Suggestions for further research is expected this can be to develop about the needs of the nutrition toddlers especially eduvation health for the mother toddlers need in develop. Keywords : Characteristics Mother, Toddler Nutritional Status Abstrak: Balita merupakan masa pertumbuhan tubuh dan otak yang sangat pesat dalam pencapaian keoptimalan fungsinya. Sehingga kebutuhan gizi balita perlu diperhatikan karena kekurangan gizi dapat mempengaruhi perkembangan otak anak. Padahal, otak tumbuh selama masa balita.Tujuan penelitian ini untuk mengetahui hubungan karakteristik ibu dengan status gizi balita yang berkunjung di puskesmas Bahu Manado. Sampel pada penelitian ini yaitu menggunakan purposive sampling sehingga jumlah sampel pada penelitian ini yaitu 98 responden. Desain Penelitian yang digunakan adalah deskriptif analitik dengan rancangan cross-sectional dan data dikumpulkan dari responden menggunakan lembar observasi. HasilPenelitian berdasarkan uji Pearson Chi Square tidak terdapat hubungan yang bermakna antara umur dengan status gizi balita (p=0.513), terdapat hubungan bermakna antara pendidikan dengan status gizi balita (p=0.001), tidak terdapat hubungan bermakna antara pekerjaan ibu dengan status gizi balita (p=0.432), terdapat hubungan bermakna antara jumlah anak dan status gizi balita (p=0.000). Kesimpulan dari penelitian menujukkan bahwa tidak terdapat hubungan umur ibu dengan status gizi balita, terdapat hubungan pendidikan ibu dengan status gizi balita tidak terdapat hubungan pekerjaan ibu dengan status gizi balita, terdapat hubungan jumlah anak dengan status gizi balita. Saran untuk peneliti selanjutnya diharapkan penelitian ini dapat menjadi bahan referensi dalam mengembangkan penelitian tentang pentingnya kebutuhan gizi pada anak balita. Kata Kunci : Karakteristik Ibu, Status Gizi Balita